EFFECT OF REACTION DURATION ON ISOPROPANOL PRODUCT (E Conference Zone, 2022)
Today, the synthesis of import-substituting organic compounds from the available resources in the country, on the basis of which the creation of solvents, disinfectants (antiseptics), antibiotics, stabilizers, fragrances in cosmetic products is an urgent task. Saturated alcohols containing С3-С5 are used in various industries as solvents, disinfectants, antibiotics, stabilizers, fragrances in cosmetic products and as additives in perfumery. Acid hydration of alkenes is one of the first classical methods for the production of alcohols. The general mechanism of the process is given below